β-Glucan-Induced Trained Immunity in Dogs - Paris, Simon; Chapat, Ludivine; Pasin, Marion; Lambiel, Manon; Sharrock, Thomas E.; Shukla, Rishabh; Sigoillot-Claude, Cecile; Bonnet, Jeanne-Marie; Poulet, Hervé; Freyburger, Ludovic; De Luca, Karelle (Frontiers in Immunology, 2020)
Several observations in the world of comparative immunology in plants, insects, fish and eventually mammals lead to the discovery of trained immunity in the early 2010’s. The first demonstrations provided evidence that innate immune cells were capable of developing memory after a first encounter with some pathogens. Trained immunity in mammals was initially described in monocytes with the Bacille Calmette-Guerin vaccine (BCG) or prototypical agonists like β-glucans. This phenomenon relies on epigenetic and metabolic modifications leading to an enhanced secretion of inflammatory cytokines when the host encounters homologous or heterologous pathogens. The objective of our research was to investigate the trained immunity, well described in mouse and human, in other species of veterinary importance. For this purpose, we adapted an in vitro model of trained innate immunity in dogs. Blood enriched monocytes were stimulated with β-glucans and we confirmed that it induced an increased production of pro-inflammatory and anti-microbial compounds in response to bacterial stimuli. These results constitute the first demonstration of trained immunity in dogs and confirm its signatures in other mammalian species, with an implication of cellular mechanisms similar to those described in mice and humans regarding cellular epigenetics and metabolic regulations.